Storage for Women’s Prayer Needs in Mosque - Marhakim, Siti Izzati; Ab Hamid, Abdullah Al Rashid (Research in Management of Technology and Business, 2026)
The purpose of this study is to identify the design criteria of a storage for women’s prayer needs in mosques and to develop a prototype to based on selected design. Maintaining indoor air quality in mosques is essential for overall environmental quality, encompassing thermal comfort and air purity. Utilizing a quantitative method, the study highlights significant issues such as inadequate airflow in storage systems, leading to moisture buildup, mold growth, and the deterioration of stored items, which compromise their quality and longevity. Current storage solutions are often insufficient, lacking space and efficient organization.This study recommends innovative approaches to spatial optimization and ergonomic design, drawing on various expert insights to create storage solutions that maximize capacity without sacrificing accessibility or visual appeal. Implementing well-ventilated and well-designed storage solutions can enhance environmental quality, preserve valuable items, and improve the user experience within mosques. By addressing these aspects, the study aims to offer a comprehensive solution to the challenges of indoor air quality and storage in mosques.